THU0095 Impact of ultrasound-detected tenosynovitis and synovitis on disease flare, disability and radiographic progression in patients with ra in clinical remission: results of the starter study. (15th June 2017) - Sakellariou, G; Filippou, G; Bellis, E; Scirè, CA; Carrara, G; Iagnocco, A; ,
Abstract : Background: In patients with RA in remission subclinical ultrasonographic (US) synovitis (-S) relates to flare and radiographic progression. The impact of tenosynovitis (-T) on flare, disability and radiographic progression is not known. Objectives: To evaluate the predictive role of US-detected tenosynovitis and synovitis in RA patients in remission on flare, disability and radiographic progression over 12-months. Methods: STARTER is a multicentre cohort study of the US Study Group of the Italian Society for Rheumatology. Participants were selected on the basis of a reliability exercise and the availability of high-end equipment with high frequencies probes. Patients with RA in remission underwent clinical and US evaluation. US -T and -S were assessed categorically by Grey Scale (GS) and power Doppler (PD) at 11 joints, extensor and flexor tendons in both hands. Patients were assesed at baseline, 6 and 12 months. The primary outcome was flare within 12 months (defined as increase in DAS28>1.2 or >0.6 if final DAS28>3.2). The secondary outcomes were progression of disability (increase ≥2.3 in the Health Assessment Questionnaire (HAQ)) and radiographic progression (increase in the total Sharp van Der Hejide score (SHS) ≥4.3) at 12 months. Logistic models were used to measure the relationship between GS-T/-S, PD-T/-S and outcomes, results were presented as odds ratios (OR) and 95% confidence interval (CI), adjusted for pre-specified confounders. Results: 361 patients (72.3% f, mean age (sd) 56.1 (13.3), median disease duration (IQR) 7.1 years (3.6–13.5)) were included, complete radiographs were available for 189/361 (52.3%) patients. 98/326 (30.6%) patients had a flare within 12 months, 70/340 (20.59%) had an increase in HAQ and 39/189 (20.6%) radiographic progression. Results are presented in Table 1 . Flare was predicted only if –T and –S, assessed by both GS and PD, were concurrently present, while both –T and-S and their combination did not predict HAQ or SHS progression. Conclusions: In patients with RA in clinical remission, US-detected synovial and tenosynovial inflammation relates to the risk of flare, while in a short term follow-up the effect on disability and radiographic progression is limited. These results might have been influenced by the short follow-up and limited power for secondary outcomes. US might integrate the clinical management of RA patients in clinical remission. Disclosure of Interest: None declared